Immunohistochemical Profiling of Immune Checkpoints in Chronic Hepatitis B Liver Tissue - João Panão-Costa; Rui Caetano Oliveira; Paulo Teixeira; Francisco Caramelo; Maria Augusta Cipriano; Olga Borges; Armando Carvalho (Pathogens)
Chronic hepatitis B (CHB) remains a significant global health concern due to complications like cirrhosis and liver cancer. Immune cell exhaustion, characterized by increased suppressive molecules and inhibitory receptors, represents a critical feature of CHB. Understanding the mechanisms of hepatic immune exhaustion in CHB patients is imperative for the development of effective therapeutic interventions. In this study, we investigated the expression levels and histological distribution of various immune checkpoint receptors and ligands in liver biopsies obtained from CHB patients. Additionally, we aimed to evaluate potential concurrent overexpression of specific receptors and their association with clinical parameters such as ALT levels. Our analysis revealed that PD-1, PD-L1, CTLA-4, TIM-3, GAL-9, CD272, TIGIT, and 2B4 exhibited predominant localization in portal tracts and sinusoids. Furthermore, we observed a correlation between the expression of PD-1, TIM-3, and GAL-9 with ALT levels in CHB patients. Additionally, a strong relationship was identified between the expression of CD272 and TIGIT, as well as between GAL-9 and CTLA-4 within the studied population. Our findings underscore the significance of the TIM-3:GAL-9 pathway in the immunopathogenesis of CHB. This detailed analysis sets the stage for future combined immunotherapy strategies aimed at leveraging checkpoint receptors to enhance clinical outcomes.